The Influence of Pengaruh Affiliate Marketing, Live Streaming, dan Purchase Urgency terhadap Perilaku Konsumsi Irasional Mahasiswa di Kota Parepare (Studi Pembelian di Aplikasi Shopee) - Rahmawati, Rahmawati; Arwin, Arwin; Umaima, Umaima; Pangestu, Dian Resky (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2025)
Digital marketing continues to evolve alongside technological and communication advancements. University students in Parepare City, as active users of social media and online shopping platforms, often exhibit irrational consumption behavior driven by emotional impulses rather than rational needs. This study aims to examine the influence of affiliate marketing, live streaming, and purchase urgency on irrational consumption behavior among Shopee users. Employing a quantitative associative approach, the research involved 100 respondents selected through quota sampling. Data were collected using a structured questionnaire and analyzed with SmartPLS 4.0 through the Structural Equation Modeling (SEM) technique. The results reveal that affiliate marketing, live streaming, and purchase urgency each exert a positive and significant influence on irrational consumption behavior. The t-test results for all variables exceeded the critical value (t > 1.96; p < 0.05), and the F-test confirmed a strong simultaneous effect. The model accounts for 70.4% of the variance in irrational consumption behavior. These findings highlight the substantial impact of digital marketing strategies on consumer decision-making and underscore the need to enhance consumption literacy among university students.